Ex-core neutron exposure monitoring and reactor internals aging management at Ringhals - Fischer Greg; Roudén Jenny; Blomström Johan; Smith Sylena (EPJ Web of Conferences)
This paper discusses the management of plant aging at the Ringhals Units 3 and 4 nuclear power plants and provides a summary of its extensive database of reactor dosimetry comparisons. Key exposure quantities of interest for reactor internals component aging evaluations are described compared to a similar plant with more typical fuel management practices. Finally, the incorporation of Ringhals exposure results into downstream thermal-mechanical calculations for Units 3 and 4 is described, as well as the relationship of these results to the reactor internals component inspection regime at Ringhals.